Mattering spiritualities
1 online resource.
Keywords: "Mattering Spiritualities brings together an array of international scholars and practitioners to explore spirituality in embodiment through the lens of performance, performative writing, and performance studies. The book concerns spirituality and takes the body as the site of whatever it is we call spirituality. The methodological assumption is that the opposition of body and spirit is a false binary that calls for re-examination and revision. It stems from the argument that people can deliberately shift their boundaries of perception and knowing through practice, technologies and performative techniques that can alter the way in which they perceive the ecologies in which they are embedded. This approach understands that careful attention to which bodies are performing in any given scenario is crucial, as is a sensitivity to the ramifications of any body's race, gender, class, and biological ability. Performance can therefore be regarded as anything through which individuals and collectives experiment with bodies as technologies. Each chapter engages with such experiments to explore how bodies experience and relate to other bodies, human and other-than-human, but also how, by mobilizing bodies and changing relationships between them, practitioners can transform people, spaces and places, objects, ecologies large and small, and shift the borders-of-the-known. Such experiments can also reveal intersectional dynamics within given social, political, and biological borders offering new perspectives and angles of analysis. This collection intends to serve transdisciplinary studies and to support varied learning and teaching environments for undergraduate, postgraduate, and PhD students"--